Strategi Sekolah Luar Biasa (SLB) Dalam Merespons Kebijakan Ketenagakerjaan Penyandang Disabilitas (Studi Kasus: SLB Negeri 2 Denpasar Tingkat SMALB - Dewi, Ni Putu Anggina Chandra; Wijaya, Komang Adi Sastra; Yudartha, I Putu Dharmanu (CITIZEN CHARTER, 2023)
Fulfillment of the right of people with disabilities to get a job is set forth in the form of a policy to provide guarantees to persons with disabilities of that right. The role of special schools (SLB) as formal educational institutions for people with disabilities is needed to prepare better quality human resources (HR) for workers with disabilities according to their main duties and functions. By implementing the right strategies by SLB, people with disabilities will be able to compete and survive in the world of work so that in the future the goals and objectives of employment policies for people with disabilities can be achieved. This study aims to find out the strategies implemented by special schools (SLB) in responding to employment policies for people with disabilities, especially in SLB Negeri 2 Denpasar. This research uses descriptive qualitative method with data collection techniques in the form of observation, interviews, and documentation. The results of this study indicate that the strategies used by SLB Negeri 2 Denpasar in responding to employment policies for people with disabilities is very good. This can be seen from the several indicators used, such as goals, environment, direction, action, and learning, which have gone very well and provided maximum results or impact on workers with disabilities.